Delivery and management of a preterm infant in the burn unit: A multidisciplinary approach. Issue 3 (May 2015) - Rodriguez, Omar; Cooma, Ruby; Cooper, Michael; Roth, Philip
Highlights Burns magnify cardiovascular and hemodynamic changes associated with pregnancy. Pharmacologic agents administered to pregnant patients affect the fetus via the placenta. A multidisciplinary team can safely deliver a preterm infant in the burn unit.